2008
DOI: 10.1589/rika.23.545
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Post Rehabilitation Outcomes of Cerebrovascular Accident Patients with Lower than 90 Points on the FIM in a Convalescence Rehabilitation Ward

Abstract: Factors Influencing Post Rehabilitation Outcomes of Cerebrovascular Accident Patients with Lower than 90 Points on the FIM in a Convalescence Rehabilitation Ward 浅川 育世 1,2) 居村 茂幸 3) 臼田 滋 1) 菅谷公美子 4) 可児 佑子 4) YASUTSUGU ASAKAWA 1,2) , SHIGEYUKI IMURA 3) , SHIGERU USUDA 1) , KUMIKO SUGAYA 4) , YUKO KANI 4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Denti et al 2) reported that the ADL level at admission was the most powerful predictor of the functional outcome of elderly stroke patients. Many studies 3,4) have addressed prediction of the outcome of patients discharged to convalescence at a rehabilitation unit. However, outcome studies of acute-phase rehabilitation have mainly been conducted of patients with cerebrovascular disease 5,6) , and there have been few studies investing other diseases such as pneumonia 7) or critically ill patients admitted to an intensive care unit (ICU) 8,9) .…”
Section: Introductionmentioning
confidence: 99%
“…Denti et al 2) reported that the ADL level at admission was the most powerful predictor of the functional outcome of elderly stroke patients. Many studies 3,4) have addressed prediction of the outcome of patients discharged to convalescence at a rehabilitation unit. However, outcome studies of acute-phase rehabilitation have mainly been conducted of patients with cerebrovascular disease 5,6) , and there have been few studies investing other diseases such as pneumonia 7) or critically ill patients admitted to an intensive care unit (ICU) 8,9) .…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies in which the FIM was used to examine the determinants of discharge to home [3][4][5][6][12][13][14][15] . Yoshida et al reported that independence in toileting largely contributed to a 79% rate of returning home 9) .…”
Section: Discussionmentioning
confidence: 99%
“…Preceding studies on factors influencing discharge to home have reported that independence in transferring, toileting, and getting on/off the toilet are predictive ADLrelated factors for patients returning home 2) . Further, the presence of daytime and nighttime caregivers, a large number of family members, and the feasibility of temporary home-stay during hospitalization have also been demonstrated to be important contributing factors [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preceding studies of factors influencing return to home have reported that independence in transfer, toileting, and getting on/off the toilet were predictive ADL-related factors for return to home 3) . Further, the presence of daytime and nighttime caregivers, a large number of family members, and the feasibility of temporarily staying at home during hospitalization have also been demonstrated to be important contributing factors [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%